2013
DOI: 10.1590/s1516-05722013000500007
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento e composição do óleo essencial de Piper aduncum L. cultivado em Manaus, AM, em função da densidade de plantas e épocas de corte

Abstract: Recebido para publicação em 21/10/2011 Aceito para publicação em 26/07/2013 RESUMO: A pimenta-de-macaco (Piper aduncum L. -Piperaceae) é uma espécie usada na medicina popular em quase todo o Brasil e apresenta alto teor de óleo essencial (2,5 a 4,0%) rico em dilapiol -éter fenílico com ação inseticida. O presente trabalho teve como objetivo contribuir para o sistema de cultivo da espécie P. aduncum nas condições de Manaus -AM. O experimento foi realizado na área experimental da Embrapa Amazônia Ocidental. O de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
4
Order By: Relevance
“…Variability in the chemical composition of an essential oil may influence its intrinsic ecotoxicity (Almeida et al 2017). While we obtained a 75.5% dillapiole composition in our P. aduncum, Silva et al (2013) reported a 85.6% dillapiole composition in P. aduncum EO from the same locality (Manaus), and Maia et al (1998) reported a proportion of dillapiole from 31.5% to 97.3% in P. aduncum samples from eight different locations in the Amazon region. This variability in EO composition data indicates that the safety parameters calculated in here are likely specific to the composition of our EO samples, and probably need to be estimated for a wider range of the EO composition spectrum in order to better establish its overall safety parameters.…”
Section: Discussionmentioning
confidence: 56%
“…Variability in the chemical composition of an essential oil may influence its intrinsic ecotoxicity (Almeida et al 2017). While we obtained a 75.5% dillapiole composition in our P. aduncum, Silva et al (2013) reported a 85.6% dillapiole composition in P. aduncum EO from the same locality (Manaus), and Maia et al (1998) reported a proportion of dillapiole from 31.5% to 97.3% in P. aduncum samples from eight different locations in the Amazon region. This variability in EO composition data indicates that the safety parameters calculated in here are likely specific to the composition of our EO samples, and probably need to be estimated for a wider range of the EO composition spectrum in order to better establish its overall safety parameters.…”
Section: Discussionmentioning
confidence: 56%
“…aduncum oil according to Silva et al (2013) is composed of dilapiol, myrcene, cis-ocimene, beta-caryophyllene and myristicin, components that may interfere with plant growth and pest and disease control. The storage and processing stages may influence the concentration of the oil, mainly environmental factors such as temperature and humidity may cause quality losses in the material, reducing or eliminating its Different letters on the bars indicate differences between means, according to the Tukey test at 5% probability.…”
Section: Resultsmentioning
confidence: 99%
“…A azadiractina, componente majoritário de A. indica, apresenta diferentes efeitos sobre cerca de 30 espécies de insetos pertencentes a diversas ordens, dependendo muito da concentração, do método de extração do OE ou pó e até da forma de colheita da espécie [14,22]. Além disso, essa substância pode afetar cerca de 200 espécies de insetos-praga, causando efeitos mínimos ou ausentes nos hospedeiros e predadores naturais dos insetos alvo, aumentando a segurança em sua utilização [19].…”
Section: Avaliação Do Potencial Repelenteunclassified